Reduction of pollutant concentrations in the plant systems with the inert filter bed. Part II: Humification of Epilobium parviflorum Schr. rhizosphere in the micro-cultivations fertilized with domestic wastewater = Redukcja stężeń zanieczyszczeń w roślinnych systemach ze złożem inertnym. Część druga: humifikacja ryzosfery Epilobium parviflorum Schr. w mikrouprawach nawożonych ściekami bytowymi - Dąbek, Zbigniew (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article details the processes accompanying transformations of organic substances in the compounds of humus rhizosphere area of Epilobium parviflorum Schr. The functions of the root organ together with root hair system were developed.
Keywords: zanieczyszczenia; próchnica; ryzosfera; Epilobium parviflorum Schr.; ścieki bytowe; mikrouprawy; złoże inertne; pollutiones; humus; domestic wastewater; keramzite